The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/1756-2171.12113
|View full text |Cite
|
Sign up to set email alerts
|

Market size and pharmaceutical innovation

Abstract: This article quantifies the relationship between market size and innovation in the pharmaceutical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(128 citation statements)
references
References 37 publications
4
107
2
2
Order By: Relevance
“…These estimates imply an elasticity of Phase I clinical trials with respect to market size of 2.4 to 4.7, bracketing Acemoglu and Linn’s estimated elasticity of 3.5 for approved new molecular entities (NMEs). However, when we consider all clinical trials combined—including Phase III trials for supplemental indications—our estimated elasticity of clinical trials with respect to market size is 3.3, rather lower than Acemoglu and Linn’s estimated elasticity of 6 for all new drug approvals, but certainly still larger than the Dubois et al (2011) estimate of about 0.25. What might explain the differences we observe here?…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…These estimates imply an elasticity of Phase I clinical trials with respect to market size of 2.4 to 4.7, bracketing Acemoglu and Linn’s estimated elasticity of 3.5 for approved new molecular entities (NMEs). However, when we consider all clinical trials combined—including Phase III trials for supplemental indications—our estimated elasticity of clinical trials with respect to market size is 3.3, rather lower than Acemoglu and Linn’s estimated elasticity of 6 for all new drug approvals, but certainly still larger than the Dubois et al (2011) estimate of about 0.25. What might explain the differences we observe here?…”
Section: Discussioncontrasting
confidence: 62%
“…First, in contrast with the U.S. market focus of both our paper and Acemoglu & Linn’s, Dubois et al (2011) estimate expected future revenues due to changes in market size using brand-name drugs’ sales revenues across 14 countries. Several of these countries regulate prescription drug prices, and regulations may change rapidly over time.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Second, as expected, we Önd that a larger population and higher GDP per capita in- 17 We also experimented with a log-logistic model that is more áexible in that it can generate a distribution with a non-monotonic hazard rate. The parameter estimates from that speciÖcation indicated that the hazard declines over time after a few weeks.…”
Section: Baseline Resultsmentioning
confidence: 76%
“…In the model and analyses that follow, I account for firm and disease-specific factors that may influence the duration of the regulatory approval process. Acemoglu and Linn (2004) find that potential market size has a strong influence on the entry of non-generic drugs and new molecular entities and DuBois et. al.…”
Section: A Model Of Approval Regulation and Firm Strategymentioning
confidence: 99%